2019
DOI: 10.31248/rjfsn2019.069
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and sensory assessment of beans pudding prepared using two different cooking methods

Abstract: The effect of cooking methods on the proximate composition and sensory properties of beans pudding (moimoi) was investigated. Two cooking methods were used; dry-heat and steam cooking method. Results for proximate analysis showed that beans pudding prepared using dry-heat cooking method had moisture content of 69.10% while the steamed method recorded 71.89% moisture. Results show that there was a significant (p<0.05) difference in the moisture, ash, fat, protein and crude fibre of the beans pudding samples. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Increased surface area corresponds to increased moisture loss; as a result, this component may be responsible for the sample's decreased moisture level. This outcome is consistent with findings by China et al (2019), who pointed out a reduction in the moisture content of bean pudding. The pudding samples from this investigation had a higher percentage of moisture than the results by China et al (2019), who observed a 71.89% moisture level in puddings.…”
Section: Moisture Contentsupporting
confidence: 93%
See 3 more Smart Citations
“…Increased surface area corresponds to increased moisture loss; as a result, this component may be responsible for the sample's decreased moisture level. This outcome is consistent with findings by China et al (2019), who pointed out a reduction in the moisture content of bean pudding. The pudding samples from this investigation had a higher percentage of moisture than the results by China et al (2019), who observed a 71.89% moisture level in puddings.…”
Section: Moisture Contentsupporting
confidence: 93%
“…The pudding samples from this investigation had a higher percentage of moisture than the results by China et al . (2019), who observed a 71.89% moisture level in puddings. The moisture content of synbiotic Brukina, which includes TN, ranged from 78.85% to 70.45% (Yeboah et al ., 2023), demonstrating similarity to the values observed in TNP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pudding is one of the processed foods made by mixing agar powder into water, milk, fruit pulp, to vegetable pulp so that it can produce a gel and has a soft texture [1]. At this time many people use fruits and vegetables in processed pudding [2,3,4,5,6]. A type of fruit that is widely used as pudding and other food is dragon fruit [7,8,9].…”
Section: Introductionmentioning
confidence: 99%